Pengaruh Pencucian Luka menggunakan Infus Daun Sirih Merah (Piper Crocatum) 40% terhadap Proses Penyembuhan Ulkus Diabetik - Wahdaniar Wahdaniar; Imran Pashar; Miladiarsi Miladiarsi (Jurnal Biomedika dan Kesehatan, 2022)
BackgroundDiabetes mellitus (DM) is a chronic metabolic disease that can cause various complications. World Health Organization data for 2019, DM is the direct cause of 1.5 million deaths, and 48% of all deaths due to diabetes occur at the age of 70 years. Data from the International Diabetes Federation (IDF), in 2021, Indonesia will be the fifth largest country with DM sufferers, with a total of around 19.64 million and an increase of about 81.8% compared to 2019. One of the complications that can be caused by diabetes mellitus is diabetic ulcers. Diabetic ulcer treatment requires a long time. Proper wound washing is an important factor in wound healing. Red betel leaf infusion can be used as a liquid to wash wounds. This study aims to analyze the effect of wound washing using 40% red betel leaf infusion on the healing process of diabetic ulcers. MethodsThe type of research used is quantitative research using the quasi method - experiment one group pre-post test. The research design is purposive sampling. This research was conducted SeptemberNovember 2017 at Semarang Independent Practice Nurses (PPM) consisting of 10 respondents. ResultsThe test results obtained a p-value of 0.024 (<0.05), meaning that there is an effect of giving red betel leaf infusion more effectively in wound healing. Therefore, this study recommends that nurses washing diabetic ulcer wounds can use 40% red betel leaf infusion. ConclusionThere is an effect of washing wounds using 40% red betel leaf infusion on the healing process of diabetic foot ulcers with a p-value of 0.024 (<0.05).